Economic indicators of conventional and ecological-based milk production - Balem, Tatiana Aparecida; Manfio, Taiza Steffanello; Machado, Ricardo Lopes; Brandão, Janaína Balk; Camara, Simone Bueno (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2023)
The global dairy sector has significant numbers: 133 million properties maintain 363 million head of cattle suitable for dairy farming, occupying 20% of the planet’s agricultural land. Since the beginning of the 1990s, dairy farming has undergone major transformations in our country, seeking to become competitive and innovative in the global market. With such importance for the economy and for many families, the control of the costs of the property is fundamental because from this it is possible to evaluate the performance of the activity and make the best decisions. The research was carried out in two dairy-producing properties, one in the process of implementing an ecological-based system with De Voisin Racional Pasture (PRV), located in the Santa Júlia Settlement, in the interior of the municipality of Julio de Castilhos-RS. The other property has a conventional production system and is located in the Community of Line One, in the municipality of Nova Palma-RS. Both properties have milk production in pasture as the main source of food for animals. Food represents the highest cost of dairy production; the use of pasture can be a cheaper food and can contribute significantly to reducing the cost of activity. The permanence of families in the dairy activity depends on cost management and management control to better manage their expenses and revenues and with this, improve the productive system practiced and / or that best suits their conditions.